Bill & Jolene - short story - Baird, Amadeline (My University, 2009)
Short story by Amadeline Baird that appeared in the 2009 edition of the University of Wisconsin-River Falls literature and art magazine, Prologue.
4 p.
Keywords: Literary work; Student literary and art publication; Prologue; Student publications--Wisconsin--River Falls; Student writing; Writing; Husbands and wives; Man-woman relationships--Fiction; Short story